Arthropoda diversity in organic cocoa farming in Bantaeng District. Issue 1 (April 2020) - Dewi, V S; A Nurariaty, A; Sulastria,; Tuwo, M
Abstract: Cocoa is an important commodity boosting national economy especially as a provider of employment, a source of income and foreign exchange. Organic cocoa cultivation can reduce production costs and benefit farmers. Farmers do not need to use inorganic fertilizers and pesticides. One of the problems faced in cocoa cultivation includes pest attacks that play a role in causing a decrease in productivity of cocoa plantations. Types of natural enemies such as insects can also play a role as biological control (a predator for other insects) that is able to suppress plant insect pest populations. The study aims to determine the type and number of arthropods found in cocoa plants that are managed organically and inorganically. The study was conducted in cocoa plantation area of Gantarang Keke Sub-district, Bantaeng District. Area of organic and inorganic cocoa plantations is ± 1 Ha. Determination of sample plants was carried out randomly using diagonal method, which was 5 replications and in each replication were 5 cocoa plants. Sampling technique is done by net method for plants that are around the plant and Pitfall traps for soil arthropods. Arthropods that were caught were then identified. Data analysis uses statistical t-test. The results showed that in organic cocoa plants, total arthropods population was 50% higher compared to inorganic cocoa farms. Arthropods that are active at soil surface are more commonly found in organic farms, namely order Hymenoptera, Formicidae family which acts as a predator.